Development of a Pediatric Visual Field Test - Miranda, Marco A.; Henson, David B.; Fenerty, Cecilia; Biswas, Susmito; Aslam, Tariq (Translational vision science & technology, 2016)
We describe a pediatric visual field (VF) test based on a computer game where software and hardware combine to provide an enjoyable test experience. The test software consists of a platform-based computer game presented to the central VF. A storyline was created around the game as was a structure surrounding the computer monitor to enhance patients' experience. The patient is asked to help the central character collect magic coins (stimuli). To collect these coins a series of obstacles need to be overcome. The test was presented on a Sony PVM-2541A monitor calibrated from a central midpoint with a Minolta CS-100 photometer placed at 50 cm. Measurements were performed at 15 locations on the screen and the contrast calculated. Retinal sensitivity was determined by modulating stimulus in size. To test the feasibility of the novel approach 20 patients (4-16 years old) with no history of VF defects were recruited. For the 14 subjects completing the study, 31 ± 15 data points were collected on 1 eye of each patient. Mean background luminance and stimulus contrast were 9.9 ± 0.3 cd/m and 27.9 ± 0.1 dB, respectively. Sensitivity values obtained were similar to an adult population but variability was considerably higher - 8.3 ± 9.0 dB. Preliminary data show the feasibility of a game-based VF test for pediatric use. Although the test was well accepted by the target population, test variability remained very high. Traditional VF tests are not well tolerated by children. This study describes a child-friendly approach to test visual fields in the targeted population.